Development of Website-Based Hybrid Learning Media to Address Learning Difficulties Among Junior High School - Dhea Lintang Suswandana; Min-Xiang Liu; Alibek Yeskermessuly; Debasish Kumar Kundu; Bridget Malasowe (Tinta Emas Publisher, 2024)
The development of website-based hybrid learning learning media is done to reduce constraints on traditional learning. The limitations of space and time dimesi become one of the shortcomings of traditional learning. Developing technological advances must also bring progress in the field of education. Therefore, currently the development of media that uses internet access is considered to be able to overcome the limitations of space and time dimensions. To overcome the limitations of the space and time dimensions, web-based hybrid learning learning media are developed. Development research conducted using the 4D model with 4 main stages, namely define, design, develop, and disseminate. Using assessments from 5 media experts. The trial was given to respondents, namely 11 grade 8 students of Muhammadiyah Middle School in Madiun City. The results of expert validation stated that website-based hybrid learning learning media met the feasibility standard as a learning medium with a percentage of 96.4%. The results of the small-scale trial also stated that the website-based hybrid learning learning media received good responses from students by 83.33%. Learning difficulties experienced by students decreased by a percentage from 83.33% to 31.57%.